Otero León, L., Pérez Rodríguez, C., Ferrari Nieto, E. y Enríquez Sánchez, J. M., (2017). Repensar los derechos humanos para una sociedad globalizada. Symposium books; 199 pp. - Neubauer Esteban, Adrian (Journal of Supranational Policies of Education (JOSPOE), 2017)
Otero León, L., Pérez Rodríguez, C., Ferrari Nieto, E. y Enríquez Sánchez, J. M., (2017). Repensar los derechos humanos para una sociedad globalizada. Symposium books; 199 pp.